High-pressure structural and vibrational properties of monazite-type BiPO4, LaPO4, CePO4, and PrPO4. (17th January 2018) - Errandonea, D; Gomis, O; Rodríguez-Hernández, P; Muñoz, A; Ruiz-Fuertes, J; Gupta, M; Achary, S N; Hirsch, A; Manjon, F J; Peters, L; Roth, G; Tyagi, A K; et al.
Abstract: Monazite-type BiPO4, LaPO4, CePO4, and PrPO4 have been studied under high pressure by ab initio simulations and Raman spectroscopy measurements in the pressure range of stability of the monazite structure. A good agreement between experimental and theoretical Raman-active mode frequencies and pressure coefficients has been found which has allowed us to discuss the nature of the Raman-active modes. Besides, calculations have provided us with information on how the crystal structure is modified by pressure. This information has allowed us to determine the equation of state and the isothermal compressibility tensor of the four studied compounds. In addition, the information obtained on the polyhedral compressibility has been used to explain the anisotropic axial compressibility and the bulk compressibility of monazite phosphates. Finally, we have carried out a systematic discussion on the high-pressure behavior of the four studied phosphates in comparison to results of previous studies.